Transcriptional analysis of Camellia Huana under low-phosphorus stress - Fan Wu; Lang Xia; Xin Xie; Yue Zhang; Biyin Pan (Scientific Reports)
Abstract The molecular mechanism underlying the response of C. huana to low-phosphorus (P) stress was explored with transcriptome sequencing to analyze the genome-wide responses of plants exposed to different durations of low-P stress. The sequencing results were validated by qRT‒PCR and analyses of related physiological and biochemical parameters. Compared with those in the control group (0 days), a significant number of genes were upregulated and downregulated in the 15-day and 30-day groups. The KEGG analysis revealed that many of these differentially expressed genes (DEGs) were enriched in sugar and energy, cytomembrane lipid, and hormone metabolism pathways. Genes involved in sugar metabolism, except for AGP (ADP pyrophosphorylase) and GBSS (granule-bound starch synthase), presented increased expression, especially β-amylase, suggesting that starch biosynthesis in C. huana under low-P stress largely depends on SP-catalyzed G-1-P. In contrast, the expression of genes involved in the EMP pathway and photosynthesis was generally inhibited under low-P stress. This stress also strongly affected cytomembrane lipid metabolism, leading to the downregulation of genes related to phospholipid metabolism and the upregulation of genes involved in sulfur lipid metabolism. Furthermore, low-P stress induced the expression of genes in the ethylene (ETH) synthesis pathway while inhibiting genes involved in the synthesis of auxin, abscisic acid, and methyl jasmonate (MeJA). The qRT‒PCR results were consistent with the transcriptome sequencing findings. Physiological and biochemical analyses revealed gradual decreases in ATP and soluble sugar levels, whereas superoxide dismutase (SOD), glutathione S-transferase, catalase (CAT), and chlorophyll levels increased. Similarly, the levels of ABA and ETH gradually increased, whereas those of IAA and MeJA decreased. The results of the analyses of physiological and biochemical parameters were similar to those of RNA-seq and qRT‒PCR. These findings provide a theoretical foundation for the potential widespread cultivation of C. huana in low-P soils.